Awareness of Artificial Intelligence Technologies and Their Relationship to Achievement Motivation among Gifted Students - Osman, Kani Salar Osman (Sulaimani Journal for Humanities, 2025)
This study investigates the relationship between awareness of artificial intelligence (AI) technologies and achievement motivation among gifted students at Azmar College for the Gifted in Sulaimaniy Governorate. It further examines the levels of AI awareness and achievement motivation, as well as potential differences based on gender and grade level. The research adopted a descriptive-analytical approach, utilizing a questionnaire as the main tool. The sample included 105 students during the academic year (2024–2025), selected through purposive convenience sampling. After reviewing related literature, the researcher developed two instruments: one to measure AI technology awareness and another for achievement motivation. Validity and reliability were verified through item analysis. The final sample comprised (100) students (62) males and (38) females, across six grades. Findings indicated a statistically significant positive correlation between AI technology awareness and achievement motivation, suggesting that greater awareness contributes to higher levels of motivation. Results also showed that students demonstrated high levels in both variables. Moreover, no significant differences were found in AI awareness or achievement motivation by gender or grade. These results align with previous studies and relevant theories, highlighting the role of AI awareness in supporting students’ drive for achievement. The study concludes with recommendations aimed at promoting AI technology awareness and fostering achievement motivation, as well as suggesting directions for future research.
Keywords: Awareness; Artificial Intelligence Technologies; Achievement Motivation; Gifted Students